2018
DOI: 10.1002/mc.22849
|View full text |Cite
|
Sign up to set email alerts
|

EWS‐FLI1 reprograms the metabolism of Ewing sarcoma cells via positive regulation of glutamine import and serine‐glycine biosynthesis

Abstract: Ewing sarcoma (EWS) is a soft tissue and bone tumor that occurs primarily in adolescents and young adults. In most cases of EWS, the chimeric transcription factor, EWS‐FLI1 is the primary oncogenic driver. The epigenome of EWS cells reflects EWS‐FLI1 binding and activation or repression of transcription. Here, we demonstrate that EWS‐FLI1 positively regulates the expression of proteins required for serine‐glycine biosynthesis and uptake of the alternative nutrient source glutamine. Specifically, we show that E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 56 publications
(127 reference statements)
0
37
0
Order By: Relevance
“…B, Tumour growth curves revealed that xenograft tumour growth in nude mice was significantly slower in shMTHFD2-treated group than that of shCtrl. [21][22][23] During the treatments of acute myeloid leukaemia and colorectal cancer, targeting MTHFD2 can markedly suppress the tumour progression both in vitro and in vivo. D, Western blot analysis of MTHFD2 in tumour xenograft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…B, Tumour growth curves revealed that xenograft tumour growth in nude mice was significantly slower in shMTHFD2-treated group than that of shCtrl. [21][22][23] During the treatments of acute myeloid leukaemia and colorectal cancer, targeting MTHFD2 can markedly suppress the tumour progression both in vitro and in vivo. D, Western blot analysis of MTHFD2 in tumour xenograft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…3 Inhibition of PSAT1 promotes DNA damage and apoptosis. 4,5 PSAT1 increases resistance in melanoma, pancreatic, and non-small cell lung cancer cells. 6 High PSAT1 expression is found in triple-negative breast cancer and is closely associated with aggressive frequently metastasizes and clinical prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, PSPH contributes to cell survival and proliferation by interacting with c‐MYC under glucose/glutamine deprivation conditions in hepatocellular carcinoma . Additionally, a high PSPH level promotes cancer cell proliferation and survival through an accumulation of reactive oxygen species and DNA damage, and facilitates brain and bone metastasis by simulating osteoclastogenesis . These findings demonstrate that PSPH may play a vital role in tumorigenesis and progression and may serve as a promising molecular target for human cancer.…”
Section: Discussionmentioning
confidence: 87%